A Highly Active Catalyst for Pd-Catalyzed Amination Reactions: Cross-Coupling Reactions Using Aryl Mesylates and the Highly Selective Monoarylation of Primary Amines Using Aryl Chlorides - Fors, Brett P. (2008)
[Image: see text] A catalyst system based on a new biarylmonophosphine ligand (BrettPhos) that shows excellent reactivity for C–N cross-coupling reactions is reported. This catalyst system enables the use of aryl mesylates as a coupling partner in C–N bond-forming reactions. Additionally, the use of BrettPhos permits the highly selective monoarylation of an array of primary aliphatic amines and anilines at low catalyst loadings and with fast reaction times, including the first monoarylation of methylamine. Lastly, oxidative addition complexes of BrettPhos are included, which provide insight into the origin of reactivity for this system.